Factors Associated with Diarrhea among Children Aged 1–4 Years - Sri Wahyuni; Henia Novianti (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Diarrhea remains a major public health problem and is one of the leading causes of morbidity and mortality among children under five years of age. Multiple maternal and environmental factors, including maternal education, exclusive breastfeeding, drinking water source, and handwashing practices, may influence the occurrence of diarrhea in young children. Identifying these associated factors is essential for developing effective prevention strategies. Purpose: To identify factors associated with diarrhea among children aged 1-4 years. Methods: A community-based analytical cross-sectional study was conducted among mothers of children aged 1–4 years in the Jeumpa Primary Health Center catchment area, Bireuen Regency, from February 2 to 21, 2026. A total of 97 respondents were selected using accidental sampling from a population of 3,488 children. Data were collected using structured questionnaires and analyzed using descriptive statistics and the Chi-square test with a significance level of 0.05. Results: Of the 97 children, 69 (71.1%) experienced diarrhea. Most mothers had secondary education (76.3%), were in early adulthood (78.4%), had provided exclusive breastfeeding (67.0%), used protected drinking water sources (75.3%), and practiced good handwashing with soap (62.9%). Maternal education (p = 0.044), exclusive breastfeeding (p = 0.001), and handwashing with soap (p = 0.012) were significantly associated with diarrhea among children aged 1–4 years. In contrast, maternal age (p = 0.422) and drinking water source (p = 0.546) were not significantly associated with diarrhea. Conclusion: Maternal education, exclusive breastfeeding, and handwashing with soap were significantly associated with diarrhea among children aged 1–4 years. Strengthening health education, promoting exclusive breastfeeding, and improving hand hygiene practices are important strategies for reducing the burden of childhood diarrhea in the community.